Clinical importance of re‐interpretation of PET/CT scanning in patients referred to a tertiary care medical centre. (25th July 2015) - Löfgren, Johan; Loft, Annika; Barbosa de Lima, Vinicius Araújo; Østerlind, Kell; von Benzon, Eric; Højgaard, Liselotte
Summary: Purpose: To evaluate, in a controlled prospective manner with double‐blind read, whether there are differences in interpretations of PET/CT scans at our tertiary medical centre, Rigshospitalet, compared to the external hospitals. Methods: Ninety consecutive patients referred to our department who had an external F‐18‐FDG PET/CT scan were included. Only information that had been available at the time of the initial reading at the external hospital was available at re‐interpretation. Teams with one radiologist and one nuclear medicine physician working side by side performed the re‐interpretation in consensus. Two oncologists subsequently and independently compared the original reports with the re‐interpretation reports. In case of 'major discordance', the oncologists assessed the respective reports validities. Results: The interpretations were graded as 'accordant' in 43 patients (48%), 'minor discordance' in 30 patients (33%) and 'major discordance' in 17 patients (19%). In 11 (65%) of the 17 cases graded as 'major discordance', it was possible to determine which report that was most correct. In 9 of these 11 cases (82%), the re‐interpretation was most correct; in one case, the original report and in another case, both interpretations were incorrect. Conclusions: Major discordant interpretations were frequent [19% (17 of 90 cases)]. In those cases where follow‐up could assess the validity, the re‐interpretation at Rigshospitalet was most correct in 9 of 11 cases (82%), indicating that there is a difference in expertise in interpreting PET/CT at a tertiary referral hospital compared to primary local hospitals.